The Effect of Casein Addition in Carbonate Apatite Mineral Crystallization - Nur Aisyah Nuzulia; Savitri Damayanti; Serin Imsa Arizuni; Yessie Widya Sari (Journal of Medical Physics and Biophysics, 2019)
Milk protein has been considered as one of the influenced factors in bone mineral crystallization. Bone mineral is mainly formed by carbonate apatite in which the crystallization process depends on the two main processes, nucleation and crystal growth. This study showed the formation of carbonate apatite by using precipitation method and observed the influence of casein, milk protein, in carbonate apatite nucleation through synthesis and crystal growth through immersion in SBF.  The result showed that carbonate apatite type B was formed by using precipitation method with chicken eggshells as calcium precursor. The addition of casein concentration could promote the apatite nucleation and crystal growth with low casein concentration ( ≤ 7.5 g.l-1) while high casein concentration addition plays role as an inhibitor.